2019
DOI: 10.1080/02670836.2019.1671645
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of WC–Co alloy properties based on thermodynamic calculation and Weibull distribution

Abstract: The influence of alloy composition and sintering temperature on the mechanical properties and reliability of WC–Co cemented carbides was studied theoretically and experimentally. For the first time, through a hybrid approach of thermodynamic calculations and Weibull distribution, the comprehensive performance of ultrafine WC–Co cemented carbides with different C contents and inhibitor type was investigated in detail. The carbon content of WC–10 wt-% Co–0.5 wt-% Cr cemented carbides was carefully controlled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Weibull distribution is proven to confer to the feeblest-link concept [ [75] , [76] , [77] , [78] ]. For brittle materials, the literature revealed that environs, production processes, and comparative factors are well-thought-out contributing factors for reliability [ [79] , [80] , [81] , [82] ]. The frequently used technique for reliability valuation is to syndicate the Weibull statistics [ 83 ].…”
Section: Overview Of Weibull Analysis (Wa)mentioning
confidence: 99%
“…Weibull distribution is proven to confer to the feeblest-link concept [ [75] , [76] , [77] , [78] ]. For brittle materials, the literature revealed that environs, production processes, and comparative factors are well-thought-out contributing factors for reliability [ [79] , [80] , [81] , [82] ]. The frequently used technique for reliability valuation is to syndicate the Weibull statistics [ 83 ].…”
Section: Overview Of Weibull Analysis (Wa)mentioning
confidence: 99%